ANALISIS SISTEM INFORMASI AKUNTANSI PENGGAJIAN KARYAWAN HONORER PADA SEKRETARIAT DPR KOTA SUBULUSSALAM - Chaliza Munasti; Nur Fadhillah Ahmad Hasibuan (UNIVERSITAS DHARMAWANGSA, 2022)
This study aims to find out how the payroll accounting information system of volunteer workers in Subulussalam City House of Representatives Secretariat works. This study uses a qualitative approach. The data types used in this study are primary data, with the data sources using the results of observations, interviews and documentation. The results of this study show that the payroll information system for temporary workers in the Subulussalam City House of Representatives Secretariat is not quite good, which due to the fact that there is no dedicated attendance registration section, may result in competing positions, and it is feared that this may lead to fraud and error.